DOMAIN KEPERCAYAAN BAHASA HALUS MASYARAKAT IBAN SEBUYAU: ANALISIS METAFORA KONSEPSI = (Faith Domain Of Subtle Language Among Iban Sebuyau Ethnic: Conceptual Metaphor Analysis) - Clinton, Ringit; Hamidah, Abdul Wahab; Remmy, Gedat (Penerbit Universiti Sultan Zainal Abidin, Malaysia (UNISZA), 2019)
The use of euphemism in daily interactions especially in the Iban community is seen as a significant challenge. This is a projection of slang, roar or coarse language usage. The phenomenon of euphemism is a very valuable medium for strengthening relationships, personal virtues or western cultures. The Iban people are no exception to using this fine language. Therefore, this paper is intended to identify the euphemism of the Iban Sebuyau based on the belief domains. Second, this paper also investigates the Sebuyau Iban community's euphemism based on the domain of belief using the Conceptual Metaphor approach. This study uses structured interviews while in the field to make the data obtained more systematic. In addition, the researcher also records the data in-situ by recording it with informants. This study found that the domain language's euphemism data is more influenced by the experience and environment of the speakers. This paper discusses the five domain of belief data as an understanding of the phenomenon of Iban Sebuyau's refined language use.